Involvement of Polyamines From Cardiac Mast Cells in Myocardial Remodeling Induced by Pressure Overload Through Mitochondrial Permeability Transition Pore Opening - Xiong, Xiaolan; Li, Junming; Zhang, Shizhong; Jia, Xiaoli; Xiao, Chao (Frontiers in Cardiovascular Medicine, 2022)
Objective To investigate the role and possible mechanisms of action of polyamines from cardiac mast cells in myocardial remodeling induced by pressure overload. Methods Pressure overload was induced by abdominal aortic constriction (AAC). Toluidine blue staining was used to visualize mast cells in cardiac tissue. The polyamine content of cardiac tissue was analyzed using high-performance liquid chromatography. Opening of mitochondrial permeability transition pore (MPTP) was determined by the Ca2+-induced swelling of isolated cardiac mitochondria, measured as a reduction in A520. Results Compared with sham rats, the cardiac mast cell density, the polyamine content (putrescine, spermidine, and spermine), and myocardial MPTP opening in rats with AAC surgery were significantly increased (P <0.05), and were accompanied by an increased myocardial fibrosis and heart weight/body weight ratio. Exogenous administration (intraperitoneal injection) of polyamines mimicked these results, and these effects were reversed by Cromolyn Sodium, a mast cell stabilizer (P <0.05). Myocardial MPTP opening increased greatly in rats with AAC surgery (P <0.05), and the three polyamines also increased myocardial MPTP opening (P <0.05). Conclusion Mast cell-derived polyamines are involved in pressure overload-induced myocardial remodeling by increasing opening of the MPTP.